2010
DOI: 10.1111/j.1365-2966.2009.15971.x
|View full text |Cite
|
Sign up to set email alerts
|

Absolute properties of the main-sequence eclipsing binary FM Leo

Abstract: First spectroscopic and new photometric observations of the eclipsing binary FM Leo are presented. The main aims were to determine orbital and stellar parameters of two components and their evolutionary stage. First spectroscopic observations of the system were obtained with DDO and PST spectrographs. The results of the orbital solution from radial velocity curves are combined with those derived from the light-curve analysis (ASAS-3 photometry and supplementary observations of eclipses with 1 m and 0.35 m tele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Our photometric parameters are consistent to within 2σ with the parameters found by Maxted & Hutcheon (2018) who solved the long-cadence K2 data. A comparison with physical parameters reported by Ratajczak et al (2010) shows remarkably good agreement, although our parameters are an order of magnitude more precise. The masses reported by Sybilski et al (2018) are consistent with our values to within 2σ, while the radii reported by them are very different.…”
Section: Fm Leosupporting
confidence: 77%
See 2 more Smart Citations
“…Our photometric parameters are consistent to within 2σ with the parameters found by Maxted & Hutcheon (2018) who solved the long-cadence K2 data. A comparison with physical parameters reported by Ratajczak et al (2010) shows remarkably good agreement, although our parameters are an order of magnitude more precise. The masses reported by Sybilski et al (2018) are consistent with our values to within 2σ, while the radii reported by them are very different.…”
Section: Fm Leosupporting
confidence: 77%
“…Here we present the full analysis of those two systems with updated physical parameters. An analysis of light-and radial velocity curves of FM Leo was published by Ratajczak et al (2010), who derived the fundamental physical parameters of the system. Updated mass measurements of the components, together with the analysis of the Rossiter-McLaughlin effect, were provided by Sybilski et al (2018).…”
Section: Sample Of Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eclipsing ephemeris of the system was first derived in Solonovich et al (2003) from their photometric data, however, the period found was 3.3643328 days that is approximately half of the currently derived period (e.g. the 6.728606 days of Ratajczak et al 2010). The absolute properties of FM Leo were studied in Ratajczak et al (2010) where the combination of photometric and spectroscopic measurements allowed for the derivation of orbital and physical parameters.…”
Section: Fm Leomentioning
confidence: 99%
“…3.1.8. EPIC 201488365 = FM Leo Ratajczak et al (2010) have published spectroscopic orbits for both components of FM Leo together with an analysis of the light curves available to them at that time. We have used the semi-amplitudes K 1 and K 2 from Ratajczak et al together with the parameters from our analysis of the Kepler K2 light curves with jktabsdim 4 to derive the absolute parameters for FM Leo given in Table 6.…”
Section: Epic 201408204mentioning
confidence: 99%